2008
DOI: 10.1111/j.1469-0691.2008.02014.x
|View full text |Cite
|
Sign up to set email alerts
|

Audit of antibiotic prescribing in two governmental teaching hospitals in Indonesia

Abstract: This article estimates the magnitude and quality of antibiotic prescribing in Indonesian hospitals and aims to identify demographic, socio-economic, disease-related and healthcare-related determinants of use. An audit on antibiotic use of patients hospitalized for 5 days or more was conducted in two teaching hospitals (A and B) in Java. Data were collected by review of records on the day of discharge. The method was validated through concurrent data collection in Hospital A. Multivariate logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
2
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 23 publications
(44 reference statements)
1
49
2
13
Order By: Relevance
“…One of the key factors is inappropriate and excessive prescription of antibiotics, including carbapenems, in the health care setting. Studies on inpatient prescription of antibiotics have been performed and published in half of the South and Southeast Asian countries, and excessive and inappropriate prescription of antibiotics in the inpatient setting has been highlighted as a major issue, ranging from between 10% to 50% of all antibiotics prescribed (97,141,(163)(164)(165)(166)(167)(168)(169). It is unlikely that the situation is better in the other countries (Bangladesh, Sri Lanka, Maldives, Bhutan, Afghanistan, Philippines, Myanmar, Laos, Cambodia, and Timor-Leste), where data are not available.…”
Section: Drivers Of Carbapenem-resistant Gram-negative Bacteriamentioning
confidence: 99%
“…One of the key factors is inappropriate and excessive prescription of antibiotics, including carbapenems, in the health care setting. Studies on inpatient prescription of antibiotics have been performed and published in half of the South and Southeast Asian countries, and excessive and inappropriate prescription of antibiotics in the inpatient setting has been highlighted as a major issue, ranging from between 10% to 50% of all antibiotics prescribed (97,141,(163)(164)(165)(166)(167)(168)(169). It is unlikely that the situation is better in the other countries (Bangladesh, Sri Lanka, Maldives, Bhutan, Afghanistan, Philippines, Myanmar, Laos, Cambodia, and Timor-Leste), where data are not available.…”
Section: Drivers Of Carbapenem-resistant Gram-negative Bacteriamentioning
confidence: 99%
“…Increasing antimicrobial resistance due to irrational use of antimicrobial agents is a serious issue worldwide [4]. Different studies have reported the inappropriate use of antimicrobial agent in developing countries [5].…”
Section: Introductionmentioning
confidence: 99%
“…2 In developing countries, antibiotics are prescribed for 44-97% of hospitalized patients, sometimes with inappropriate dosages. 3 Inappropriate usage of antibiotics (incorrect indications, selection, duration of administration, and dosage) may cause side effects, such as allergies or diarrhea, increase health care costs, and increase the possibility of selection for antibioticresistant bacterial strains. 2 Group A β-hemolytic streptococcus (GABHS) or Streptococcus pyogenes is the most common cause of acute bacterial pharyngitis.…”
mentioning
confidence: 99%